Hydrogen production by dark fermentation from pre-fermented depackaging food wastes. (January 2018) - Noblecourt, Alexandre; Christophe, Gwendoline; Larroche, Christian; Fontanille, Pierre
Graphical abstract: Highlights: Characterization of depackaging wastes. Production of hydrogen and volatile fatty acids with pre-fermented substrate. Biological hydrogen potential tests with a factorial fractional design. Modeling of hydrogen production by Gompertz model. Abstract: In this study, a specific fraction of food waste, i.e. depackaging waste, was studied as substrate for hydrogen production by dark fermentation. During storage and transport of this liquid mixture, inhibitory compounds like acids or alcohol might be produced by endogenous flora. A factorial fractional design based on the composition of the substrate was used to determine the best condition to convert this substrate into hydrogen. First results indicated that the consortium used might convert high quantity of lactate into hydrogen. A batch culture confirmed that lactate was used as the main carbon source and a global yield of 0.4molH2 ·mollactate −1 was obtained. This study demonstrated the ability of the consortium tested to convert different carbon sources (carbohydrates or lactate) with good efficiency. These data represented an important parameter in the prospect of using an industrial substrate whose composition is liable to vary according to the conditions of storage and transport.